Using stories of change to monitor and evaluate impacts of the techno gabby program in Eastern Visayas, Philippines - Cagasan, Editha G. (The Philippine Journal of Development Communication, 2009)
A new participatory monitoring and evaluation approach, known as the Most Significant Change (MSC) technique or Story Approach, was used to monitor impacts or the changes experienced by stakeholders of the Techno Gabay Program (TGP) in Eastern Visayas, Philippines. Impact monitoring was done for one year across nine Techno Gabay (TG) centers. Implementation of the MSC process was guided by the procedures outlined by Davies and Dart (2005). Results revealed that the sharing of significant change stories generated through the MSC technique was able to facilitate communication and learning about program impacts among the different TGP stakeholders. Participants of the pilot-testing activities perceived the MSC technique as a learning tool that could: (1) enable te TG field staff to know their clients better; (2) allow field staff to understand the outcomes of their efforts; (3) give insights that can guide stakeholders in improving the program; (4) inspire the staff upon knowing that they did something good; and (5) enable the staff to share program outcomes with others through stories. Some factors, however, appeared to limit the usefulness of the MSC technique in the context of TGP-EV. These include the stakeholders' perception that program monitoring using the MSC process is an added work which competes with their regular work assignments; the perception of some stakeholders that stories are difficult to write; and the muting of some voices in the process of making sense of program impacts.